High Cholesterol Prevention through Healthy Lifestyle Education and the Use of Bay Leaves (Syzygium polyanthum) as a Cholesterol-Lowering Herbal Remedy in Islamic Boarding Schools - Tri Wahyuni Bintarti; Hotimah Masdan Salim; Nanda Fadhilah Witris Salamy; Machmudah Machmudah; Audi Ikhfina Tanra Aji; Rangga Azhaar Faraadies; Khadijah Khairul Bariyah (UKInstitute, 2026)
Hypercholesterolemia is a growing health problem, including among adolescents in Islamic boarding schools (pesantren) where diets are high in fat and low in fiber, and physical activity is limited. This condition carries a risk of developing cardiovascular disease, necessitating preventive interventions tailored to the characteristics of the Islamic boarding school community. This Community Service (PkM) activity aims to increase students' knowledge and awareness of high cholesterol prevention through healthy lifestyle education and the use of bay leaves (Syzygium polyanthum) as an alternative herbal cholesterol-lowering agent. The program's innovation lies in integrating evidence-based health education with local wisdom, making it easily implemented in Islamic boarding schools. The activity was conducted at the Zainul Hasan Genggong Islamic Boarding School in Probolinggo in May 2025, involving 30 students and 14 religious teachers. The methods used included an initial survey, FGDs, interactive counseling with pre- and post-test evaluations, and free health checks, including anthropometry, blood pressure, and blood sugar measurements, medical consultations, and medication administration. The primary outcome was increased participant knowledge, measured by comparing pre-test and post-test scores and baseline health data from the examination. The results of the activity showed an average increase in participant knowledge of 23.4 points between the pre-test and post-test. Students also gained practical skills in using bay leaves as a daily ingredient beneficial for health.